Diseño de un Plan de Respuesta para la conservación y mejoramiento en caminos de acceso en la Línea de Transmisión Moín-Cahuita- Sixaola del ICE - Ramírez-López, Adrián (Instituto Tecnológico de Costa Rica, 2014)
This Graduation Project (GP) was developed as a Professional Guided Practice modality, it was carried out in the Ways Construction Area from the UEN PySA, specifically in the Instituto Costarricense de Electricidad (ICE). This work contributes to the improvement of several procedures that involve conservation and penetration way´s enhancement in the transmission line from Moín-Cahuita-Sixaola. The project is based on a reply plan for conservation and penetration way´s enhancement through administrative aspects and technical emphasis evaluation; all this according to national laws and field needs. The administrative approach takes into consideration the internal planning procedures and the Project Management Institute´s good administration practices by means of the PMBOK ® guide. The technical emphasis considers the control tools. For construction procedures, many tools were made, as: flowcharts, evaluation sheets and verification lists. The material mentioned was supplemented by field viewings and it was validated in new projects from the area. Finally, a good practices for penetration way´s construction guide was obtained, it is a compilation of recommendations for evaluating constructive procedures in aspects like environment, work organization, machinery and cement stabilized bases.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2014.
Keywords: Evaluación; PMI; Base Estabilizada; Red de Caminos; Rehabilitación